iRhom2 and TNF: Partners or enemies? - Badenes, Marina (2020)
iRhom2 is an essential cofactor for ADAM17, the metalloprotease that sheds both the proinflammatory cytokine tumor necrosis factor-α (TNF-α) and TNF receptors (TNFRs) from the cell surface. In this issue of Science Signaling, Sundaram et al. demonstrate a protective role for iRhom2 in promoting ADAM17-mediated shedding of TNFRs in hepatic stellate cells, which reduces TNFR signaling and liver fibrosis in response to injury.